Pengaruh Komunikasi Dan Hubungan Industrial Terhadap Kepuasan Kerja Karyawan Pada Hotel Fave Petitenget Kabupaten Badung Bali - I Ketut Merta; Anak Agung Elik Astari; Ni Kadek Ernawati Kertagam (Universitas Mahendradatta Denpasar, 2018)
In the research result, analysis and discussion about the problem of influence between independent variable and dependent by using methodology of multiple regression analysis, the number of respondents 78 people from the total population, can be explained as follows: Communication Variables (X1) partially significant effect on variable Satisfaction employee work (Y). With the t test on the Communication variable produces: t count of 3.202 and significance of 0.002. t arithmetic 3.202 t table whose value is 1.663 with significance level 0.173 0.05, it can be seen that the hypothesis that Communications have a significant positive effect on employee job satisfaction. So that communication take the role of doniman in employee job satisfaction. Variable of Industrial Relations (X2) partially significant result t count equal to 5,349 and significance equal to 0,000. t count 5.349 t table whose value is 1.663 with significance level 0.173 0.05, it can be seen that the hypothesis expressing industrial relations have a significant positive effect on employee job satisfaction, this proves industrial relations run harmonious .. Hypothesis accepted by t arithmetic 1.377 t table 0.663, then the hypothesis which states that there is a significant positive influence between communication and industrial relations with employee job satisfaction. With the good relationship to the two variables so that employee job satisfaction can run well, further research can be done on other occasions with variables outside this research.